River water quality management using mathematical modelling - Vieira, J. M. Pereira (1996)
The river Cavado basin, located in the north-western region of Portugal, has a very intensive use for water supply, irrigation and hydropower generation. In the last years pollution of water has increased due to industrial and domestic wastewater discharges, and, simultaneously, new water treatment plants (WTP) (Braga, Esposende), and wastewater treatment plants (WWTP) (Vila Verde, Amares, Braga, Esposende) have been installed. A mathematical model has been calibrated and run for a range of River Cavado flow conditions to predict river water quality changes after pollutant loads. Biochemical oxygen demand (BOD), dissolved oxygen (DO) and faecal coliforms (FC) bacteria were used as water quality control parameters to assess critical situations near the proposed site for the construction of a new water treatment plant for the portuguese metropolitan area of Oporto.